Editor's Choice – Outcome of Radical Surgical Treatment of Abdominal Aortic Graft and Endograft Infections Comparing Extra-anatomic Bypass with In Situ Reconstruction: A Nationwide Multicentre Study. (December 2021) - Gavali, Hamid; Mani, Kevin; Furebring, Mia; Olsson, Karl W.; Lindström, David; Sörelius, Karl; Sigvant, Birgitta; Gidlund, Khatereh D.; Torstensson, Gustav; Andersson, Manne; Forssell, Claes; Åstrand, Håkan; et al.
Abstract : Objective: Abdominal aortic graft and endograft infection (AGI) is primarily treated by resection of the infected graft and restoration of distal perfusion through extra-anatomic bypass (EAB) or in situ reconstruction/repair (ISR). The aim of this study was to compare these surgical strategies in a nationwide multicentre retrospective cohort study. Methods: The Swedish Vascular Registry (Swedvasc) was used to identify surgically treated abdominal AGIs in Sweden between January 1995 and May 2017. The primary aim was to compare short and long term survival, as well as complications for EAB and ISR. Results: Some 126 radically surgically treated AGI patients were identified – 102 graft infections and 24 endograft infections – treated by EAB: 71 and ISR: 55 (23 neo-aorto-iliac systems, NAISs). No differences in early 30 day (EAB 81.7% vs . ISR 76.4%, p = .46), or long term five year survival (48.2% vs . 49.9%, p = .87) were identified. There was no survival difference comparing NAIS to other ISR strategies. The frequency of recurrent graft infection during follow up was similar: EAB 20.3% vs . ISR 17.0% ( p = .56). Survival and re-infection rates of the new conduit did not differ between NAIS and other ISR strategies. Age ≥ 75 years (odds ratio [OR] 4.0, confidence interval [CI] 1.1 – 14.8), coronary artery disease (OR 4.2, CI 1.2 – 15.1) and post-operative circulatory complications (OR 5.2, CI 1.2 – 22.5) were associated with early death. Prolonged antimicrobial therapy (> 3 months) was associated with reduced long term mortality (HR 0.3, CI 0.1 – 0.9). Conclusion: In this nationwide multicentre study comparing outcomes of radically treated AGI, no differences in survival or re-infection rate could be identified comparing EAB and ISR.